2023
DOI: 10.7759/cureus.37450
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Medical Students’ Perceptions of Psilocybin-Assisted Therapy for Use in Medical Practice

Abstract: BackgroundPsilocybin use, along with other psychedelics, has seen an increased interest among professionals in the medical community due to its potential therapeutic benefits for psychiatric disorders, substance use disorders (SUD), and palliative care. While it is certain that more research is necessary as psychedelicassisted therapy becomes more prevalent, it will most likely be future physicians at the forefront of this neoteric care. Currently, physicians receive minimal training because of psilocybin's co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(25 citation statements)
references
References 28 publications
4
6
0
Order By: Relevance
“…The researchers then adapted the medical cannabis instrument to assess the attitudes about psilocybin among medical students [25]. The results of this study showed that medical students with a greater selfassessment of their knowledge about medical psilocybin, less concern for its potential adverse effects, and the opinion that psilocybin should be federally legalized for recreational purposes have more positive attitudes about its medical use.…”
Section: Instrumentmentioning
confidence: 98%
See 4 more Smart Citations
“…The researchers then adapted the medical cannabis instrument to assess the attitudes about psilocybin among medical students [25]. The results of this study showed that medical students with a greater selfassessment of their knowledge about medical psilocybin, less concern for its potential adverse effects, and the opinion that psilocybin should be federally legalized for recreational purposes have more positive attitudes about its medical use.…”
Section: Instrumentmentioning
confidence: 98%
“…To our knowledge, there are few published reports of the perceptions, knowledge, and attitudes of healthcare professionals in general and pharmacists and/or trainees regarding psilocybin-assisted therapy [25][26][27]. Mental health professionals tend to have unfavorable attitudes and minimal self-rated expertise in psilocybin [28].…”
Section: Knowledge and Attitudes About Psilocybin Among Pharmacistsmentioning
confidence: 99%
See 3 more Smart Citations